Local structure of the convective boundary layer measured by a volume-imaging radar - Pollard, Brian David (ScholarWorks@UMass Amherst, 1998)
For over 30 years, radars have examined the structure of the convective boundary layer (CBL). Those studies have consisted either of the three dimensional structure of km-scale features, or of the vertical structure of local, 1 to 100 m-scale features. A new instrument, the Turbulent Eddy Profiler (TEP), images the local, three dimensional character of the CBL with the 10 m-scale resolution of current vertically profiling systems. This thesis presents TEP CBL measurements, including $\tilde C\sbsp{n}{2}$, the local refractive index structure-function parameter, and w, the vertical velocity. Qualitative horizontal and vertical images are shown. The scales of the measured structures are then quantified through calculation of the correlation distance. To examine larger scale features, effective volumes are constructed from TEP time series data through Taylor's hypothesis. Within those volumes, the statistical properties of $\tilde C\sbsp{n}{2}$ and w and calculated. These measurements highlight some of the capabilities of the TEP system, and give a unique picture of the morphology and evolution of $\tilde C\sbsp{n}{2}$ and w in the CBL. Many of the TEP measurements are compared to appropriately scaled large-eddy simulation (LES) predictions. The LES qualitative CBL structure agrees well with the measurements, while the statistical values of $\tilde C\sbsp{n}{2}$ agree well for only some of the measured data. Those $\tilde C\sbsp{n}{2}$ comparisons are the first of their kind, however, and suggest that LES may become a useful tool in CBL propagation studies.